Functional imaging of cognition in an old-old population: A case for portable functional near-infrared spectroscopy - Huppert, Theodore J.; Karim, Helmet; Lin, Chia-Cheng; Alqahtani, Bader A.; Greenspan, Susan L.; Sparto, Patrick J. (My University, 2017)
In this study, functional near-infrared spectroscopy (fNIRS) was used to record brain activa- tion during cognitive testing in older individuals (88±6yo; N = 19) living in residential care communities. This population, which is often associated with loss of personal independence due to physical or cognitive decline associated with aging, is also often under-represented in neuroscience research because of a limited means to participate in studies which often take place in large urban or university centers. In this study, we demonstrate the feasibility and initial results using a portable 8-source by 4-detector fNIRS system to measure brain activity from participants within residential care community centers. Using fNIRS, brain sig- nals were recorded during a series of computerized cognitive tests, including a Symbol Digit Coding test (SDC), Stroop Test (ST), and Shifting Attention Test (SAT). The SDC and SAT elicited greater activity in the left middle frontal region of interest. Three components of the ST produced increases in the right middle frontal and superior frontal, and left superior frontal regions. An association between advanced age and increased activation in the right middle frontal region was observed during the incongruent ST. Although none of the partici- pants had clinical dementia based on the short portable mental status questionnaire, the group performance was slightly below age-normed values on these cognitive tests. These results demonstrate the capability for obtaining functional neuroimaging measures in resi- dential settings, which ultimately may aid in prognosis and care related to dementia in older adults.